The Influence of Placement and Work Climate on Employee Performance and It’s Implications on the Performance of A Property Company in Bireuen City - Rizky Putra; Hafasnuddin; Iskandarsyah (International Journal of Asian Business and Management, 2024)
The purpose of this research is to determine the placement conditions, work climate, employee performance, and company performance, as well as the influence of placement on company performance, the influence of work climate on company performance, the influence of placement on employee performance, the influence of work climate on employee performance, the influence of employee performance on company performance, the influence of placement on company performance through employee performance, and the influence of work climate on company performance through employee performance. The object of this research is the placement and work climate towards employee performance and its implications on company performance. The data analysis tool used in this research is descriptive testing to test descriptive statistical models based on mean values and verificative testing using the structural equation modeling (SEM) data analysis tool with the assistance of the AMOS program. The research results indicate that placement, work climate, employee performance, and company performance are running well. There is an influence of placement and work climate on employee performance, an influence of employee performance on company performance, an influence of placement and work climate on company performance, and also an influence of placement and work climate on company performance through employee performance. This research was conducted on a Property Company in Bireuen City